TINGKAT KESUKAAN DAN NILAI GIZI ROLADE IKAN TENGGIRI (SCOMBEROMORUS SP) DENGAN PENAMBAHAN TEMPE DAN WORTEL SEBAGAI MAKANAN SELINGAN ANAK USIA SEKOLAH - Shofiyah, Irbah (Jurnal Gizi dan Kesehatan Nusantara, 2024)
School children aged 7-12 years are one of the groups vulnerable to nutritional problems. An imbalance in the nutritional needs can lead to nutritional issues, whether it be undernutrition or overnutrition. Therefore, a snack product that is not only delicious but also healthy and nutritious is needed, one of which is roulade. The alternative ingredients used in this study are spanish mackerel with the addition of tempeh and carrots. The aim of this study is to determine the level of preference and nutritional value of the best roulade with the addition of tempeh and carrots as an alternative snack for school-age children. This research is an experimental study with the following formulas: P1 - 400 g Spanish Mackerel, 50 g Tempeh, 50 g Carrot; P2 - 350 g Spanish Mackerel, 100 g Tempeh, 50 g Carrot; P3 - 350 g Spanish Mackerel, 75 g Tempeh, 75 g Carrot. The results of the preference test showed that spanish mackerel roulade with the addition of tempeh and carrots affects the level of preference in terms of taste, color, aroma, and texture. The results of the nutritional content test of the best roulade product per 100 grams are: energy = 177.83 kcal, protein = 11.97 g, fat = 6.87 g, carbohydrates = 17.03 g.